2017
DOI: 10.1155/2017/1603450
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Magnetic Properties of Ni Doped ZnS Diluted Magnetic Semiconductors Synthesized by Hydrothermal Method

Abstract: Diluted magnetic semiconductors Zn 1− Ni S with different consistency ratio ( = 0, 0.01, 0.03, 0.05, and 0.07) were successfully synthesized by hydrothermal method using ethylenediamine as a modifier. The influence of Ni doping concentration on the microstructure, morphology, and optical and magnetic properties of undoped and Ni doped ZnS nanocrystals was characterized by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), X-ray energy dispersive spectrometry (XEDS), ultraviolet-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…5. The polarization characteristics are identified by Raman spectroscopy with satisfactorily recognized indication of acoustic and optical modes [17,23]. There are two pronounced bands observed at 263 cm -1 and 347 cm -1 , which are identified as transverse optical (TO) and longitudinal optical (LO) modes, respectively.…”
Section: Raman Spectroscopymentioning
confidence: 90%
See 2 more Smart Citations
“…5. The polarization characteristics are identified by Raman spectroscopy with satisfactorily recognized indication of acoustic and optical modes [17,23]. There are two pronounced bands observed at 263 cm -1 and 347 cm -1 , which are identified as transverse optical (TO) and longitudinal optical (LO) modes, respectively.…”
Section: Raman Spectroscopymentioning
confidence: 90%
“…The present observations implied that Ni dopant does not influenced on the lattice structure of nanocrystals and it corroborates with the TEM observations. However, it is observed that the Raman peaks are shifted toward lower energy (Table 2) as compared to the bulk ZnS values [23][24][25][26], which signify quantum confinement effects on synthesized Ni0 NCs and Zn Ni S x 1-x NCs. )…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The FTIR results showed several absorption bands in the region 4000 -400 cm -1 , the spectrum shows peaks at 415.585, 661.464, 1004.73, 1138.76,1629.55, and 3441.35 cm -1 . The peak at 3441.35 cm -1 and 1629.55 cm -1 related to OH groups that were surrounding around the nanoparticle, the peak at 3441.35 cm -1 related to OH stretching vibration, and the peak at 1629.55 cm -1 related to H-O-H bending (Sabaghi et al 2018), the peak at 1138.76 related to S-O impurities (Sabaghi et al 2018), the peak at 1004.73 may be corresponding to the organic compounds (Wu et al 2017), the peaks at 405 cm −1 and 661.464 cm -1 are the characteristic absorption of Zn-S bond (Shaikh and Sonawane. 2016), (Kumar and Upadhyay.…”
Section: Fourier Transform Infrared Measurementmentioning
confidence: 99%
“…For example, depending on the crystalline quality of the AlN substrate ZnO deposited films show an epitaxial growth [19,20]. Extensive studies have been reported on ZnS nanostructures doped with different transition metal ions (such as Co, Mn, Ni, Fe) prepared by different techniques [21][22][23][24]. Depending on the type of dopant ion, the doped materials exhibit different luminescent, electronic and magnetic properties.…”
Section: Fig 1 the Cubic Unit Cell Of Zinc Blende (A) And The Hexagmentioning
confidence: 99%